Integration of Emotional Intelligence in the Implementation of Curriculum and Islamic Boarding School-Based Learning: Educational Implications for Sustainable Development: Integrasi Emotional Intelligence dalam Pelaksanaan Kurikulum dan Pembelajaran Berbasis Pesantren: Implikasi Pendidikan untuk Pembangunan Berkelanjutan - Wildan Agus Wicaksono (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2024)
This study aims to develop the perspective of integrating emotional intelligence values in the implementation of pesantren-based curriculum and its implications for education for sustainable development. This research was developed by the researcher with the initial concept, namely efforts to develop students' emotional intelligence through curriculum management and learning which was then re-analyzed on the implications of education for sustainable development. This study uses a qualitative approach of multi-site study type at the research location or site I, An-Nur Bululawang Junior High School and site II, Al-Yasini Pasuruan Superior Junior High School. The results of this study show that the integration of emotional intelligence in the pesantren-based curriculum, in this case at An-Nur Bululawang Junior High School and Al-Yasini Superior Junior High School, has great potential to support sustainable development goals, in aspects related to students' emotional intelligence.